They are: nth term = 6n-4 and the 14th term is 80
1, 1, 2, 3, 5, 8, 13, 21, ...Restate the question: What are the terms of the Fibonacci sequence?The Fibonacci sequence is formed by beginning with the first two terms both equal to one. From there on, each term is found by adding the two previous terms:1+1=2, 1+2=3, 2+3=5, 3+5=8, 5+8=13, 8+13=21, ...
Let n (i) = the term number of each term in the sequence., with (i) going from 1-6 E.g term number 1 (n (1) ) is 3. n(2)= -7 etc... Therefore n(i) for odd terms in the sequence is n (i)= (n (i -2)th term +1). For even terms in the sequence, n(i)= (n (i - 2)th term -3).
This is the Fibonacci sequence, where the number is the sum of the two preceding numbers. The nth term is the (n-1)th term added to (n-2)th term
Assuming each term is 3 MORE than the previous term t(n) = -13 + 3*n where n = 1, 2, 3, ...
They are: nth term = 6n-4 and the 14th term is 80
13 This is because each term of the sequence is determined by adding the 2 previous terms of the sequence. This particular sequence is called the Fibonacci Sequence, and has special properties. See related link.
The general term of the sequence 2, 4, 2, 4, 2, 4 is repeating number sequence.
1, 1, 2, 3, 5, 8, 13, 21, ...Restate the question: What are the terms of the Fibonacci sequence?The Fibonacci sequence is formed by beginning with the first two terms both equal to one. From there on, each term is found by adding the two previous terms:1+1=2, 1+2=3, 2+3=5, 3+5=8, 5+8=13, 8+13=21, ...
To find the nth term of a sequence, we first need to determine the pattern or rule that governs the sequence. In this case, the sequence appears to be increasing by adding consecutive odd numbers: 3, 6, 9, 12, and so on. Therefore, the nth term formula for this sequence is Tn = 3n^2 + n. So, the nth term for the sequence 4, 7, 13, 22, 34 is Tn = 3n^2 + n.
It is: 1 1 2 3 5 8 13 and 21 which is the 8th term
Let n (i) = the term number of each term in the sequence., with (i) going from 1-6 E.g term number 1 (n (1) ) is 3. n(2)= -7 etc... Therefore n(i) for odd terms in the sequence is n (i)= (n (i -2)th term +1). For even terms in the sequence, n(i)= (n (i - 2)th term -3).
The general term for the sequence 0, 1, 1, 2, 2, 3, 3 is infinite sequence.
It Depends if the sequence was 5,7,9,11,13 the term to term rule wud be start at 5 and add 2 each time till you get 13. Hope this helps! :D
This is the Fibonacci sequence, where the number is the sum of the two preceding numbers. The nth term is the (n-1)th term added to (n-2)th term
Assuming each term is 3 MORE than the previous term t(n) = -13 + 3*n where n = 1, 2, 3, ...
recursive rule: term(n+1) = term(n) + (n) also, n starts at 0 and term(1)=3 term(1) = 3 ; (n=0) term(2) = term(1) + (1) = 4 term(3) = term(2) + (2) = 6 term(4) = term(3) + (3) = 9 term(5) = term(4) + (4) = 13 . . .